(3MQGS GdCcaGOhddeLGgO YGeQ Ydj eGbhQI (B:s (3GdKhQI GdJMQjQjI GdcHQi aj GdhdGjI GdKGdKI(B1957-1962 /s - (3YGeQ, RGgjIs ((3GdLRGFQ (B:s (3OGQ GdMceI ddJQLeI h GdfTQ ,s, 2012)
(3YGeQ Ydj GdedbH Ydi eGbhQI ef ehGdjO(B08 (3SHJeHQ HbQjI eGbhQI ef ehGdjO(B08 (3SHJeHQ (B1938 (3HbQjI eGbhQI OhGQ RcQj GdJMb HUaha LjT GdJMQjQ aj SHJeHQ(B1957 (3h aj (B1960 (3YjfI bGFO GdhdGjI GdKGdKI GdYbjO Sj eMfO hdMGO Vef MQSg GdNGU h ehaOg GdGefj HYO GdGSJbdGd GfNQW aj GdLjT GdhWfj GdTYHj djJbGYO Yfg SfI(B1990(3HQJHI bGFOs
Keywords: (3GdKhQI GdJMQjQjIs; (3GdeLGgO YGeQ Ydj eGbhQIs; (3GdCcaGOhs